2011
DOI: 10.1038/onc.2011.412
|View full text |Cite
|
Sign up to set email alerts
|

Four proteins governing overangiogenic endothelial cell phenotype in patients with multiple myeloma are plausible therapeutic targets

Abstract: Bone marrow (BM) angiogenesis has an important role in the initiation and progression of multiple myeloma (MM). We looked at novel mechanisms of vessel formation in patients with MM through a comparative proteomic analysis between BM endothelial cells (ECs) of patients with active MM (MMECs) and ECs of patients with monoclonal gammopathy of undetermined significance (MGECs) and of subjects with benign anemia (normal ECs). Four proteins were found overexpressed in MMECs: filamin A, vimentin, a-crystallin B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…In particular, it has been demonstrated that FLNA physically interacts with HIF-1a (Zhenga et al 2014), that regulates angiogenesis through upregulation of vascular endothelial growth factor (VEGF) (Uramoto et al 2010, Berardi et al 2011, Semenza 2012. Whereas VEGF-driven angiogenesis may play an important role in endocrine tumourigenesis and tumour progression (Hanahan et al 1996) and several in vitro studies suggested that SS analogues display potent antiangiogenic properties (Woltering et al 1991, Barrie et al 1993, Danesi & Del Tacca 1996, Kumar et al 2004, we showed that SST2 agonist reduced VEGF protein levels and release, but this inhibitory effect was totally abolished in the absence of FLNA.…”
Section: Discussionmentioning
confidence: 78%
“…In particular, it has been demonstrated that FLNA physically interacts with HIF-1a (Zhenga et al 2014), that regulates angiogenesis through upregulation of vascular endothelial growth factor (VEGF) (Uramoto et al 2010, Berardi et al 2011, Semenza 2012. Whereas VEGF-driven angiogenesis may play an important role in endocrine tumourigenesis and tumour progression (Hanahan et al 1996) and several in vitro studies suggested that SS analogues display potent antiangiogenic properties (Woltering et al 1991, Barrie et al 1993, Danesi & Del Tacca 1996, Kumar et al 2004, we showed that SST2 agonist reduced VEGF protein levels and release, but this inhibitory effect was totally abolished in the absence of FLNA.…”
Section: Discussionmentioning
confidence: 78%
“…The MGUS patients (23 male and 12 female), ages 42 to 79 (median 60.5) years, were IgG (n ¼ 22), IgA (n ¼ 8), and k or l (n ¼ 5). Normal (control) endothelial cells were derived from 12 subjects with anemia due to iron or vitamin B 12 deficiency (20). The study was approved by the Ethics Committee of the University of Bari Medical School (Bari, Italy), and all patients provided their informed consent in accordance with the Declaration of Helsinki.…”
Section: Patients and Endothelial Cellsmentioning
confidence: 99%
“…Chemotaxis. MMECs (5 Â 10 4 ) were tested in a Boyden microchamber assay toward DMEM with 1.5% fetal calf serum alone (negative control) or added with VEGF (10 ng/mL; Sigma Chemical Co.), and FGF-2 (10 ng/mL; Peprotech Inc.) as chemoattractants (20). After 8 hours at 37 C, the migrated cells were fixed, stained, and counted by the EVOS inverted microscope (EuroClone) at Â400.…”
Section: Functional Studiesmentioning
confidence: 99%
“…After 18 hours, the skeletonization of the mesh was followed by measurement of mesh areas and vessel length in three randomly chosen Â200 fields on an EVOS digital inverted microscope (Euroclone; ref. 18). Three different doses of SU11274 (0.1, 0.5, and 1 mmol/L), bortezomib (7.5, 10, and 20 nmol/L), and lenalidomide (0.5, 0.25, and 1.75 mmol/L) were singularly tested in the Matrigel assay.…”
Section: Functional Studiesmentioning
confidence: 99%
“…Real-time RT-PCR was performed using primers (Invitrogen) shown in Supplementary Table S1, and the Applied Biosystems methodology (18). Relative quantification of the mRNA was performed using the comparative threshold cycle (C t ) method with GAPDH as the reference gene and with the 2 ÀDDCt formula (19).…”
Section: Elisa Immunoprecipitation Western Blot Analysis and Real-mentioning
confidence: 99%